The 'Bloomfield Movement Classification': Motion analysis of individual players in dynamic movement sports - Bloomfield, J.; Polman, R.; O'Donoghue, P. (International Journal of Performance Analysis in Sport, 2004)
It is critical to employ sound scientific principles of physical conditioning and coaching in order to enhance sports performance. One of the most critical of these principles is the rule of specificity. To this end the specific requirements of the performance must be investigated to elicit a high degree of transfer from competition into a training regime which optimises performance in competition. One useful method of investigating physical requirements of sport is time-motion analysis where various modes of motion are subjectively or objectively chosen and timed throughout the performance. To date, fewer than 8 modes of motion have often been chosen in time-motion investigations, however it is arguable that this does not provide a high enough degree of specificity to detail the physical demands of a sport. In this paper, we outline a new approach to timemotion analysis through a method involving 14 modes of timed-motion, 3 'other' non-timed movements, 14 directions, 4 intensities, 5 turning categories and 7 'On the Ball' activity classifications known as the 'Bloomfield Movement Classification' (BMC). The BMC is performed through computerised video-analysis and is highly specific, accurate and reliable. The details of the method are explained within this paper.